2008
DOI: 10.1186/1472-6831-8-14
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusion, psycho-social impacts and treatment need: A cross-sectional study of Tanzanian primary school-children

Abstract: Backgroundstudies on the relationship between children's malocclusion and its psycho-social impacts are so far largely unexplored in low-income countries. This study aimed to assess the prevalence of malocclusion, reported dental problems and dissatisfaction with dental appearance among primary school children in Tanzania. The relationship of dissatisfaction with socio-demographic characteristics, clinically defined malocclusion and psychosocial impacts of dental anomalies was investigated. Orthodontic treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
3
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 29 publications
8
18
3
4
Order By: Relevance
“…This concurs with Locker who found that there were disparities in OHQoL among a group of Canadian schoolchildren, with children from low income households having the poorest OHQoL (26). M M concerns about their dental appearance are influenced by the social and cultural context in which they live (29).…”
Section: The Effect Of Socio-economic Statussupporting
confidence: 82%
“…This concurs with Locker who found that there were disparities in OHQoL among a group of Canadian schoolchildren, with children from low income households having the poorest OHQoL (26). M M concerns about their dental appearance are influenced by the social and cultural context in which they live (29).…”
Section: The Effect Of Socio-economic Statussupporting
confidence: 82%
“…A prevalência da insatisfação com a aparência dos dentes e gengivas nos adolescentes foi de 11,4% sendo menor quando comparada a países tão díspares como Tanzânia (23,3%) 19 , Nigéria (57,4%) 2 e Turquia (42,7%) 20 . No entanto, as comparações devem ser feitas com cautela devido às diferenças metodológicas existentes, como as diferentes faixas etárias estudadas, tipos de índices utilizados ou formas de categorização das variáveis 3 .…”
Section: Discussionunclassified
“…Um dos principais achados deste estudo foi o aumento da proporção de indivíduos insatisfeitos com a aparência dos dentes e gengivas conforme o aumento da gravidade das oclusopatias. Este achado reforça a relevância de considerar as medidas subjetivas quando se pretende identificar os problemas oclusais que provocam impacto negativo na vida dos adolescentes 19 . Considerando que o tratamento ortodôntico foi incluído no elenco de alternativas terapêuticas especializadas do Sistema Úni-co de Saúde, o diagnóstico das oclusopatias possui dois objetivos principais: avaliar a necessidade e a prioridade de tratamento dos indivíduos, e obter informações para alocar adequadamente os recursos necessários para a provisão do tratamento ortodôntico para a população 24 .…”
Section: Discussionunclassified
“…8 However, the majority of the studies that investigated the impact of malocclusion on OHRQoL focused on adolescents with permanent dentition. [3][4][5][8][9][10][11][12][13][14][15][16][17][18] As children's feelings about their dental appearance begin early, at about 8 years of age, children have criteria similar to those of adults regarding the selfperception of body image. Occlusal changes may occur in the mixed dentition and affect self-image.…”
Section: Introductionmentioning
confidence: 99%